2020
DOI: 10.1155/2020/8826087
|View full text |Cite
|
Sign up to set email alerts
|

The Retinal Inner Plexiform Synaptic Layer Mirrors Grey Matter Thickness of Primary Visual Cortex with Increased Amyloid β Load in Early Alzheimer’s Disease

Abstract: The retina may serve as putative window into neuropathology of synaptic loss in Alzheimer’s disease (AD). Here, we investigated synapse-rich layers versus layers composed by nuclei/cell bodies in an early stage of AD. In addition, we examined the associations between retinal changes and molecular and structural markers of cortical damage. We recruited 20 AD patients and 17 healthy controls (HC). Combining optical coherence tomography (OCT), magnetic resonance (MR), and positron emission tomography (PET) imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…An increasing number of studies have investigated whether retinal neuronal measurements are associated with brain measurements at various stages of AD. The findings are inconsistent, with some studies finding an association between retinal and brain measurements (Jorge et al, 2020; López-de-Eguileta et al, 2022; Mauschitz et al, 2022; Mejia-Vergara et al, 2021; Méndez-Gómez et al, 2018; Mutlu et al, 2018, 2017; Shi et al, 2020, 2019; Uchida et al, 2020), some finding no association (Casaletto et al, 2017; den Haan et al, 2019), and others with inconclusive results (Donix et al, 2021). However, methodological differences may explain some of this inconsistency—systematic differences between OCT or MRI devices across manufacturers and models, choice of parameters and settings, and the wide range of measurements which can be acquired from each of these technologies make comparison across studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have investigated whether retinal neuronal measurements are associated with brain measurements at various stages of AD. The findings are inconsistent, with some studies finding an association between retinal and brain measurements (Jorge et al, 2020; López-de-Eguileta et al, 2022; Mauschitz et al, 2022; Mejia-Vergara et al, 2021; Méndez-Gómez et al, 2018; Mutlu et al, 2018, 2017; Shi et al, 2020, 2019; Uchida et al, 2020), some finding no association (Casaletto et al, 2017; den Haan et al, 2019), and others with inconclusive results (Donix et al, 2021). However, methodological differences may explain some of this inconsistency—systematic differences between OCT or MRI devices across manufacturers and models, choice of parameters and settings, and the wide range of measurements which can be acquired from each of these technologies make comparison across studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a modest correlation between brain PET SUVr and retinal spot count, suggesting a pathologically relevant relationship between the brain and the retina. While a recent study suggests a relationship between the primary visual cortex and the inner plexiform layer of the retina, 25 multiple regions of the neocortex were measured to calculate SUVr in this current study. Future retinal imaging study designs may consider measuring other brain regions associated with the retina, such as the lateral geniculate and primary visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SPECT imaging is greatly improved by the integrated use of visual assessment and statistical analysis. Non-radioisotopic probes for imaging AD include [ 19 F] fluoride Congo red and [ 19 F] curcumin mimetics [11,12]; perfluoro agents, such as styrylbenzoxazole analogs have also emerged [12]. Among the tested compounds, the styrylbenzoxazole compound linked with seven ethylene glycol groups in the PEG (polyethylene glycol) chain showed significant [ 19 F]MR signals in the brains of AβPPswe/PS1dE9 mice compared to wild type (WT) counterparts.…”
Section: Of 12mentioning
confidence: 99%
“…An alternative to these limitations is afforded by the recent discovery of Abeta deposition in the retinae of humans diagnosed with AD [ 17 ], as well as in the retinae of preclinical mouse models [ 18 ]. In a clinical study, comparing the retinal functions of AD patients ( n = 20) versus healthy people ( n = 17) using PET, MRI, and optical coherence tomography (OCT), the work showed that the retinae are also found with increased Abeta load in early AD [ 19 ]. The proof-of-concept clinical imaging for the detection of Abeta in the retinae was explored recently using a commercially available curcumin-based Longvida probe [ 20 ].…”
Section: Introductionmentioning
confidence: 99%